Codes of Medical Ethics - Malik, A (Oxford University Press, 2017)
Codes serve to regulate and set standards for professionals to follow, and informs society of the conduct expected of professionals [1]. The term medical ethics was not coined till 1803 when Thomas Percival wrote his eponymous book [2, 3], however the foundation of medical morality, informed by culture, philosophy and religion, was laid by oaths and treatise in the premodern era. It is therefore not unreasonable to speak of a long tradition of medical ethics prevailing in many places over many centuries and though the language may differ from time to time and culture to culture [4], some features exhibit atemporality. The purpose of this chapter is to trace the evolution of Islamic medical ethics’ codes and treatises from Pre-modern to Post-Modern times. Beginning with the genesis of Akhlāq and Ādāb treatise in the pre-modern era followed by the codes developed in the post-modern era by the Islamic Organization for Medical Sciences. In order to provide the framework within which the codes are written I discuss, albeit briefly, the normative principles derived from Shari’a.